Influence of management intensity and environmental conditions on microbiota in biological soil crust and crust-free soil habitats of temperate forests. (May 2020) - Ngosong, Christopher; Buse, Thomas; Ewald, Martin; Richter, Andreas; Glaser, Karin; Schöning, Ingo; Ruess, Liliane
Abstract: The microbiota in three distinct terrestrial habitats (biological soil crusts – BSC, crust-adhering soil beneath BSC – trans, and crust-free soil close to BSC – soil) was studied in 33 temperate forest stands differing in management intensity (ForMI). Specific lipid fractions and respective marker fatty acids were used to determine microbial biomass and community structure (phospholipid fatty acids – PLFA), energy reserves (neutral lipid fatty acids – NLFA), and community level lipid profiles (CLLP) of nematodes and enchytraeids. The density and diversity of nematode fauna were additionally determined morphologically. The highest total amounts of PLFA and NLFA occurred in the BSC, followed by soil and trans habitats, indicating stronger effects of habitats than forest management intensity. This corresponds to the distribution pattern of bacterial PLFA that dominated the soil microbiota. The highest nematode population density occurred in the BSC, followed by soil and trans. The BSC was dominated by bacterial feeders and omnivores, while plant feeding nematodes were most frequent in the crust-free soil habitat. The highest biomass of photoautotrophs also occurred in the BSC, followed by the crust-adhering and crust-free soil habitats. Redundancy analysis indicated strong effect of ForMI and total N on soil PFLAs and NFLAs across habitats. The C:N and C:S ratios were important for the separation of NLFAs while P:S accounted for the separation of PLFAs. Bacterial and fungal PLFAs largely separated the microbial community across habitats, and particularly between BSC and trans habitats. The separation of nematodes and enchytraeids by CLLP was less pronounced, and most distinct between the crust-free soil and BSC or crust-adhering soil habitats. Overall, BSC and crust-adhering soil habitats provide different suitability for microbiota, resulting in specifically adapted communities that are shaped by the management intensity and nutrient availability. Highlights: Forest management intensity shape biological soil crust with different microhabitats. Greater effect of habitats on soil microbiota than forest management intensity. Bacterial and fungal PLFAs separated microbial communities across habitats. High nematode density in crust, dominated by omnivores and bacteria feeders.